1998
DOI: 10.1002/(sici)1096-8652(199810)59:2<133::aid-ajh6>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic transforming growth factor-beta in patients with bone marrow fibrosis—pathophysiological implications

Abstract: Idiopathic myelofibrosis (IMF) and secondary myelofibrosis (MF) are characterized by bone marrow (BM) fibrosis, neoangiogenesis, and increased extracellular matrix (ECM) proteins. These characteristics may be partially attributed to transforming growth factor beta (TGF-), a cytokine produced by monocytes. In myelofibrosis, monocytes are increased and activated with concomitant up-regulation of intracytoplasmic TGF-. We have therefore determined systemic TGF-in patients with either BM fibrosis: IMF, n = 18; MF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“…16,19,21 TGFβ1 regulates osteoblast differentiation and plays a key role in tissue repair. 17,18 We found that TGFβ1 expression was significantly higher in the group D than the control group, consistent with earlier results. Van Leeuwen et al showed that production of osteocalcin and osteopontin by osteoblasts was stimulated by vitamin D. 19 We found that osteopontin expression was significantly higher in the group D than control group, again consistent with earlier results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…16,19,21 TGFβ1 regulates osteoblast differentiation and plays a key role in tissue repair. 17,18 We found that TGFβ1 expression was significantly higher in the group D than the control group, consistent with earlier results. Van Leeuwen et al showed that production of osteocalcin and osteopontin by osteoblasts was stimulated by vitamin D. 19 We found that osteopontin expression was significantly higher in the group D than control group, again consistent with earlier results.…”
Section: Discussionsupporting
confidence: 91%
“…13,14,43 Positive effect of vitamin D on bone; It increases TGF synthesis and release, regulates osteoblast differentiation, stimulates tissue repair and osteocalcin and osteopontin production. [16][17][18][19][20][21] The use of vitamin D to accelerate fracture healing will allow an early return to daily activity by, and reduce the morbidity of, patients with condylar fractures associated with osteoporosis. We explored the effects of a single high-dose systemic injection of vitamin D on condylar fracture healing in osteoporotic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated elevated intracellular levels of TGFβ‐1 in platelets, megakaryocytes, and peripheral blood mononuclear cells as well as higher plasma concentrations in patients with IMF 23–26 and provide clinical evidence for a potential pivotal role of TGFβ‐1 in bone marrow fibrosis. However, there is a lack of data regarding TGFβ‐1 gene expression level in haematopoiesis, megakaryocytes, as well as total bone marrow cells, in different CMPD subtypes.…”
Section: Discussionmentioning
confidence: 76%
“…Transforming growth factor‐β is a potent profibrotic cytokine and extensive evidence has shown that its overexpression plays a crucial role in mediating the fibrotic process, 12,20 including pulmonary fibrosis, 21 pneumoconiosis, 22 radiation fibrosis, 23 myelofibrosis, 24 peritoneal adhesions 25 and hypertrophic scarrings 26 . Conversely, strategies targeted at neutralizing TGF‐β activity can reduce fibrotic damage in the lung, 27–29 liver 30,31 and skin 32 .…”
Section: Discussionmentioning
confidence: 99%